The military and the Muslim Brotherhood: Will a power-sharing agreement be reached in Egypt? - Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2012)
The lower house of Egyptian parliament, the People's Assembly, convened for its first meeting on January 23, 2012. But that did not bring the political protests in the country to an end. Many of the predominantly young activists fear that the military will not withdraw from the political process. They accuse the generals of delaying the country's political reorganization and of showing no interest in the development of a democratic state - a view shared by actors across the political spectrum. Yet the majority of elected parties decided against a position of fundamental opposition. In particular, the Freedom and Justice Party (FJP) - which represents Egypt's Muslim Brotherhood, the clear winner in the lower house elections - is apparently seeking a power-sharing arrangement with the military leadership. Since the military probably does not want to continue bearing sole political responsibility, such a power-sharing arrangement is likely. Whether this will serve as a stable foundation for successful and sustained political and economic transition, however, remains uncertain
Keywords: 320